Eribulin and sintilimab combined with radiotherapy in a heavily pretreated patient with advanced retroperitoneal myxoid pleomorphic liposarcoma: a case report and literature review - Zhuo, Hongyu; Li, Dongna; Fu, Yang; Zhang, Xinyao; He, Xin; Xu, Ying; Liu, Jie; Jiang, Yu; Deng, Yaotiao (Frontiers in Oncology, 2025)
Myxoid pleomorphic liposarcoma (MPLPS) is an ultra-rare subtype of soft tissue sarcoma. The limited number of reported cases has led to significant challenges in its clinical management. Here, we present the case of a 52-year-old woman diagnosed with advanced retroperitoneal MPLPS. As first-line therapy, she underwent 4 cycles of chemotherapy with doxorubicin and ifosfamide. Anlotinib was subsequently added to the first-line regimen. Following this, she received gemcitabine plus albumin paclitaxel as second-line therapy. Notably, a partial response (PR) was achieved and sustained for 12 months following the administration of eribulin and sintilimab combined with radiotherapy. The demonstrated effectiveness of this multidisciplinary approach underscores its potential as a novel treatment strategy for patients with advanced MPLPS. To our knowledge, this article represents the first detailed documentation of multidisciplinary diagnosis and treatment of MPLPS.